„Jest nas coraz więcej i coraz więcej będzie nas umierać”. O Grochowie Andrzeja Stasiuka - Żórawska, Natalia (Postscriptum Polonistyczne, 2020)
Andrzej Stasiuk’s collection of short stories Grochów (2012) is a sentimental reminiscence of the author’s childhood and youth. Stasiuk recalls events from the past: happiness and ease are replaced by pain, loneliness, sickness and death. The author of the article explains how the feeling of emptiness and loss is created by the writer, for whom the idea of loss is the main theme of the book. The aim of the text is to interpret Grochów, according to the category of trauma and the attempt to present Stasiuk’s creativity through the torments of the past.